Simultaneous Determination of Lead and Cadmium in Biological Samples by Multichannel Graphite Furnace Atomic Absorption Spectrometry - IMAI, SHOJI; HAYASHI, YASUHISA; SAITO, KENGO; ISHIKURA, HIROSHI; TANAKA, TOSHIYUKI (Eisei kagaku, 1991)
A simple and rapid method was investigated for the determination of μg/l levels of lead and cadmium in biological samples, by multichannel graphite furnace atomic absorption spectrometry using ammonium dihydrogen phosphate as a matrix modifier. Bovine whole blood and human serum were selected as biological samples for application. The method has a detection limit of 0.36 μg/l for lead and 0.026 μg/l for cadmium. Concentration of lead 788±14 μg/l and cadmium 13.4±0.1 μg/l in a certified reference material, bovine blood, was in good agreement with the certified value (lead 772±11 μg/l ; cadmium 12.4±0.5 μg/l), respectively. This method was applied to ten sera of normal subject and levels of lead (3.3±1.0 μg/l) and cadmium (0.28±0.11 μg/l) obtained showed reasonable values.